The Prototype of National Projects is the “Health” Program of the Kalmyk ASSR in the 1980s - Margarita V. Baduginova (Монголоведение)
Introduction. The study is devoted to the development and implementation of comprehensive targeted programs “Health” that appeared in the regions of the country in the 1980s. Their emergence is associated with the time of cardinal changes in the spheres of social policy and health care in the USSR and RSFSR, as well as in the light of the implementation of the decisions of the XXVII Congress of the CPSU. The purpose of the article is to examine the structure and implementation of the complex program “Health” in the territory of the Kalmyk ASSR in the 1980s under the existing historical conditions. Materials and methods. The main source base for the study were the documents deposited in the funds R-9 of the Ministry of Health of the Kalmyk ASSR, R-90 of the State Planning Committee of the KASSR, R-309 of the Council of Ministers of the KASSR of the National Archive of the Republic of Kalmykia. The article used normative-legal acts, as well as periodicals that covered the issue of program measures in the field of health, published in the 1980s. The work was prepared using both general scientific and special methods of historical research: systematic, comparative, quantitative, retrospective, as well as the principles of objectivity, reliance on historical sources and historicism. Results. The social sphere came to the forefront of the country's policy due to the fact that in the 1980s there was a need to reform the health care system in the RSFSR and the USSR. The republican complex program “Health” was developed for the period 1986–1990 and its main tasks were to provide the population with high quality medical, preventive and medicinal assistance. Conclusions. The emerging “Health” programs were supposed to significantly improve the health care situation in the country. But the problems accumulated over decades in the economy, ecology and social sphere required a more qualitative and serious approach, which was not solved by the creation of formal complex programs. As the political situation in the Soviet Union began to become unstable, this program could no longer ensure the normal functioning of the deteriorating health care system.